THE INFLUENCE OF WORK ENVIRONMENT, WORK DISCIPLINE, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. OPAL COFFEE INDONESIA - Pesta Sihombing; Andre Fitriano; Julienda Br Harahap (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research has a background to achieve the author's goal, namely to study and explain the effect of work environment, work discipline, and work motivation on employee performance at PT Opal Coffee Indonesia. The results obtained by researchers in the influence of the work environment, work discipline and work motivation on employee performance in the company are not maximized enough. Therefore, research is carried out using scientific methods. Simple random sampling is a method that researchers use to select samples from a simple random population type. Thus the number of respondents studied was 50 employees at PT. Opal Coffee Indonesia. The first process is done by measuring the answers to sample data using validity tests and reliability tests. Furthermore, the results of the data test are measured by the classical assumption test (normality test, multicollinearity test, heteroscedasticity test) and hypothesis testing using the t test partially, simultaneous F test and multiple linear regression test. The results in this study, partially there is a work environment, work discipline and work motivation have a significant effect on employee performance at PT Opal Coffee Indonesia. Simultaneously work environment, work discipline and work motivation have a positive and significant effect simultaneously on employee performance at PT Opal Cofee Indonesia. Keywords: work environment, work discipline, work motivation, employee